2014
DOI: 10.1525/jer.2014.9.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from South and East Asia on Clinical and Research Ethics: A Literature Review

Abstract: A review was conducted of English-language peer-reviewed and gray literature on health and ethics written by authors from Bangladesh, China, India, and Pakistan. This was supplemented by the knowledge of co-authors who are involved in bioethics capacity building in these countries. Of the identified literature that focused on the application of Western principles, it largely discussed informed consent and revealed norms in clinical decision-making that include physician paternalism, family involvement in decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…A literature review on South Asian perspectives on clinical and research ethics reported that medical paternalism persists in South Asian society. 49 Recruitment involving senior physicians or researchers through partnerships between hospitals and academic centres is preferred to recruitment by individuals with perceived lesser hierarchical status by South Asians living in the UK. 50 While this dynamic may be beneficial for increasing numbers where physician recruitment is feasible, potential abuse of this power dynamic may be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review on South Asian perspectives on clinical and research ethics reported that medical paternalism persists in South Asian society. 49 Recruitment involving senior physicians or researchers through partnerships between hospitals and academic centres is preferred to recruitment by individuals with perceived lesser hierarchical status by South Asians living in the UK. 50 While this dynamic may be beneficial for increasing numbers where physician recruitment is feasible, potential abuse of this power dynamic may be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…In the LMIC emergency care setting, it is also particularly important to be aware of the power dynamics between clinicians and patients or their surrogates. The recommendations of clinicians may carry undue weight by virtue of their perceived expertise and authority 40. This influence is likely to be at its greatest when time is short and patients and families are extremely vulnerable and looking for guidance.…”
Section: The Ethics Of Emergency Care Researchmentioning
confidence: 99%
“…This reflexively nudges participants to pay attention to the potential benefits and risks of genetic analysis for their ethnic communities. It is too simplistic to say that ethical decision-making in East Asian countries is more family- or community-centered than Western countries (Akabayashi and Slingsby, 2006; Chen et al, 2013), but it is nevertheless true that family and community considerations are important in clinical practice and research in East Asia (Pratt et al, 2014). Like in Africa (Ramsay et al, 2014), community approval would not supersede individual informed consent in East Asia.…”
Section: Comparative Analysismentioning
confidence: 99%